Requirement of a putative mitochondrial GTPase, GemA, for azole susceptibility, virulence, and cell wall integrity in Aspergillus fumigatus - Zhou, Xiaogang; Yang, Guorong; Li, Chengxi; Yang, Fan; Chang, Xuelian (Frontiers in Microbiology, 2022)
Drug resistance in fungal pathogens is a new challenge in clinical aspergillosis treatment. Mitochondria as dynamic organelles are involved in numerous biological processes in fungi, including drug resistance. However, little is known about the mechanism underlying mitochondrial regulation of the response of fungal pathogens to antifungal drugs. Here, we showed that a putative mitochondrial GTPase, GemA, a yeast Gem1 homolog, is crucial for the azole response and cell wall integrity in the opportunistic pathogen Aspergillus fumigatus. The fluorescence observation showed that GFP-labeled GemA is located in mitochondria, and loss of gemA results in aberrant giant mitochondrial morphology and abnormal mitochondrial membrane potential. Moreover, a ΔgemA mutant attenuates fungal virulence in the Galleria mellonella model of aspergillosis. Furthermore, gemA loss increases resistance to azoles and terbinafine but not to amphotericin B. Of note, RNA-seq combined with RT-qPCR showed that a series of drug efflux pumps were upregulated in the gemA deletion mutant. Deleting mdr1 or inhibiting the expression of drug efflux pumps can partially decrease the resistance to azoles resulting from the gemA mutant, implying that GemA influences azole response by affecting the expression of drug efflux pumps. Importantly, the ΔgemA mutant is susceptible to the cell wall-perturbing reagent CR, but not to CFW, and this defect can be partly rescued by hyperosmotic stress. TEM revealed that the cell wall of ΔgemA was thicker than that of the WT strain, demonstrating that GemA plays a role in cell wall composition and integrity. Collectively, we identified a putative mitochondrial GTPase, GemA, which is critical for hyphal growth, virulence, azole susceptibility, and cell wall integrity and acts by affecting mitochondrial function.